The Impact of Colorectal Conditions on Psychosocial Well Being of Caregivers and Patients Presenting to A Tertiary Care Hospital - rasul, laraib; Fiaz, Mudassar; shahwar, ameena; fatima, mehak; iftikhar, usama; raza, Rafee; faraz, omer; liaqat, naeem; Jahangir, jawad (Iranian Journal of Pediatric Surgery, 2023)
Colorectal conditions such as Hirschsprung disease, anorectal malformation, fecal incontinence and spinal condition cause a significant stress among patients and their caregivers. Managing such disorders requires not only a one-time definitive surgery but a significant number of follow up visits, dietary modifications and long-term medication. The aim of this study was to estimate the psychosocial wellbeing of caregivers and patients suffering from these conditions.